2019
DOI: 10.4067/s0717-95022019000200612
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Morphological Characteristics and Body Composition between Different Team Players from Serbian Junior National League: Soccer, Handball, Basketball and Volleyball

Abstract: MASANOVIC, B.Comparative study of morphological characteristics and body composition between different team players from Serbian junior national league : soccer, handball, basketball and volleyball. Int. J. Morphol., 37(2):612-619, 2019. SUMMARY:The purpose of this study is to define every subsample with precision, to give an overview of the importance of the differences between different team players, as well as to point to the closeness along with the remoteness between them, and finally, to determine latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 22 publications
4
27
0
3
Order By: Relevance
“…Results of this study indicate a strong difference regarding body height among handball and volleyball players on one side and subjects from the control group on the other side which is consistent with previous studies (Taborski, 2007;Lidor & Ziv, 2010). Different type of activity and game rules can explain the observed difference between handball and volleyball players (Masanovic, 2019). However, the worrying fact is that there is no significant difference among handball players and subjects from the control group, because research shows that body height is very important for success in elite handball .…”
Section: Discussionsupporting
confidence: 91%
“…Results of this study indicate a strong difference regarding body height among handball and volleyball players on one side and subjects from the control group on the other side which is consistent with previous studies (Taborski, 2007;Lidor & Ziv, 2010). Different type of activity and game rules can explain the observed difference between handball and volleyball players (Masanovic, 2019). However, the worrying fact is that there is no significant difference among handball players and subjects from the control group, because research shows that body height is very important for success in elite handball .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies that have analysed the entire population confirm that there is a specific correlation coefficient in males (r=0.691) and females (r=0.629) from Kosovo (Popovic 2019). However, some recent studies have also confirmed that the regional differences between the same ethnic groups also exist (Popovic, 2017;Masanovic, 2019), which caused the need for additional caution. Therefore, the main goal of this research was to investigate the above-mentioned facts, and test their validity for Western-Kosovans, that is, for one of the five Kosovan regions.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this, they are even more important when we want to diagnose individuals with abnormalities in growth or standing height loss during surgical procedures on the spine (Mohanty, Babu, & Nair, 2001), as well as to anticipate standing height in people who are too old to stand properly, thus making it very difficult to measure precisely, and sometimes impossible because of problems with movement and kyphosis (Bjure, Grimby, & Nachemson, 1968;Chumlea, Roche, & Steinbearagh, 1985;Popovic, Gardasevic, Masanovic, Arifi, & Bjelica, 2017). Finally, this information is of vital importance in sport, since the standing height represents a significant factor that influences the success in almost all sports disciplines Gusic, Popovic, Molnar, Masanovic, & Radakovic, 2017;Masanovic, 2019;Arifi, Bjelica, Masanovic, 2019).…”
mentioning
confidence: 99%
“…It is a highly dynamic and fast team game that, with its richness of movement, falls under the category of polystructural sports games Bjelica, Popovic, Gardasevic, & Krivokapic, 2016). Soccer is a sport that is characterized by numerous and various complex and dynamic kinesiological activities, which are then characterized by either cyclical Gusic, Popovic, Molnar, Masanovic, & Radakovic, 2017;Gardasevic, Bjelica, & Vasiljevic, 2017) or acyclical movement (Masanovic, 2019;Gardasevic, Bjelica, Milasinovic i Vasiljevic, 2016;. In sport, top scores can be achieved only under conditions of well-programmed training process (Gardasevic, Akpinar, Popovic, & Bjelica, 2019;Bjelica, Popovic, Tanase, & Gardasevic, 2017;Bojanic, Petkovic, Gardasevic, Muratovic, & Vasiljevic, 2015).…”
Section: Introductionmentioning
confidence: 99%